2021
DOI: 10.3390/metabo11020100
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metabolomic Assessment of the Sub-Lethal Toxicity of Halogenated Acetic Acids (HAAs) to Daphnia magna

Abstract: Halogenated acetic acids (HAAs) are amongst the most frequently detected disinfection by-products in aquatic environments. Despite this, little is known about their toxicity, especially at the molecular level. The model organism Daphnia magna, which is an indicator species for freshwater ecosystems, was exposed to sub-lethal concentrations of dichloroacetic acid (DCAA), trichloroacetic acid (TCAA) and dibromoacetic acid (DBAA) for 48 h. Polar metabolites extracted from Daphnia were analyzed using liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 96 publications
(159 reference statements)
0
3
0
Order By: Relevance
“…In our experiments, alterations in the TCA cycle, the urea cycle and metabolism of amino acids were highlighted as perturbed with intensity of stress. Although our analysis was a preliminary discovery analysis and not targeted to any pathway, targeted methods have identified perturbations in specific pathways [ 54 ] or mapped these changes on specific tissues [ 55 ] in these crustaceans. Furthermore, this study focused on a composite mixture as a stress pool and not on a specific chemical; however, lithium, for example, has been recently assessed in its nanoparticle form to affect amino acid, starch and glucose metabolism, which could also be reflected in our study from changes in the relevant catabolic enzymes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, alterations in the TCA cycle, the urea cycle and metabolism of amino acids were highlighted as perturbed with intensity of stress. Although our analysis was a preliminary discovery analysis and not targeted to any pathway, targeted methods have identified perturbations in specific pathways [ 54 ] or mapped these changes on specific tissues [ 55 ] in these crustaceans. Furthermore, this study focused on a composite mixture as a stress pool and not on a specific chemical; however, lithium, for example, has been recently assessed in its nanoparticle form to affect amino acid, starch and glucose metabolism, which could also be reflected in our study from changes in the relevant catabolic enzymes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although PFHxA and PFHxS shared many similarities in their respective metabolic responses, there were also unique secondary responses observed with each pollutant (Figures 2 and 4). Halogenated carboxylic acid–bearing pollutants have been found to perturb purine and TCA cycle pathways in aquatic organisms including D. magna (Berends et al, 1999; Labine et al, 2022; Labine & Simpson, 2021). The polar functionality of PFAS, including carboxylic acid–bearing pollutants such as PFBA, PFHxA, and PFNA, could lead to the formation of hydrogen bonds between the pollutant and nucleotides, impeding the formation of structural hydrogen bonds between other nucleotides and leading to DNA base‐pair mutations (Chou et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To examine how BPA, BPF and BPS sub-lethal exposure may alter D. magna metabolism, this study used a targeted liquid-chromatography with tandem mass spectrometry (LC-MS/MS) method to compare metabolic responses of BPA with its analogues, BPF and BPS. This method targets polar metabolites, including amino acids, sugar derivatives, carboxylic acids, nucleosides, nucleotides, vitamins, polyamines, and neurotransmitters [50,51]. Previous studies involving D. magna showed that exposure to BPA elicits disruptions to amino acid and energy metabolism pathways [39,40].…”
Section: Introductionmentioning
confidence: 99%